Reframing Recognition in Organizations - Matthew Sowcik; Hannah Carter; Valerie McKee (EDIS)
Business leaders today are faced with the challenges associated with employee engagement, recruitment, and retaining top talent. One answer that has emerged to address these challenges has been employee recognition programs. Although research has pointed to the numerous benifits associated with recognition programs, many organizations still struggle to create and deliver effective recognition programs. Many of these programs fail due to the lack of structure enabling employees to recognize each other, difficulty selecting individuals to recognize, lack of clarity concerning program objectives, and company cultures that do not support recognition. This article looks at utilizing Bolman and Deal’s four frame model (including structural, human resources, political, and symbolic) to provide leaders with a better understanding of recognition programs and guidance regarding changes a program can undergo to more accurately match the organizational landscape.